Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10:
ISBN 13:

Chapter 9 - Basic Algebra - Review Exercises - Page 697: 63

Answer

$= -1$

Work Step by Step

$=\frac{3-(5^{2} - 4^{2})}{14 + 24\div (-3)}$ $=\frac{3-(25-16)}{14 -8}$ $=\frac{3-9}{14 -8}$ $=\frac{-6}{6}$ $=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.